Association between tubal ligation and endometrial cancer risk: A Swedish population‐based cohort study. Issue 1 (13th February 2018) - Falconer, Henrik; Yin, Li; Altman, Daniel
Abstract : Tubal ligation results in less advanced stages and lower risk of metastatic spread at diagnosis of endometrial cancer (EC) but the primary preventive effect of the procedure is unclear. In a Swedish nationwide population‐based cohort study, we crosslinked registry data for tubal ligation, EC, and death for Swedish women between 1973 and 2010. All women were followed until EC, emigration, hysterectomy for non‐cancerous reasons, death, or end of follow‐up. Primary outcome was incidence of EC and secondary outcome overall survival. We calculated adjusted incidence rates (IR) per 100, 000 person‐years and hazard ratios (HR) using Cox regression models. A total of 35, 711 cases of EC were identified among 5, 385, 186 women. The IR of EC among exposed was 17.7 (95% CI 15.7–19.9) versus 29.0 (95% CI 28.7–29.3) among unexposed (per 100, 000 women years). Exposed individuals had significantly reduced risk of EC (HR 0.73, 95% CI 0.65–0.83). The mortality rate among women with EC was 72% lower in exposed compared to unexposed (IR 1, 441; 95% CI 1, 089–1, 907 and IR 5, 136; 95% CI 5, 065–5, 209, respectively) which following adjustment corresponded to a HR of 0.71 (95% CI 0.49–1.03). Tubal ligation was associated with lower risk of EC as well as mortality rates in women with EC. Elective tubal ligation may be adopted in future cancer preventive strategies but must be balanced against the irreversibility of the procedure, which preclude further unassisted reproduction. Abstract : What's new? Tubal ligation is associated with lower stage and reduced mortality among women with endometrial cancer. Whether tubal ligation has subsequent effects on endometrial cancer risk, however, remains unclear. In this population‐based study of women in Sweden, tubal ligation was associated with a significantly decreased risk of subsequent development of endometrial cancer, as well as with reduced mortality from the disease. The effect was most evident for aggressive tumors. The findings suggest that tubal ligation constitutes an effective measure for the prevention of endometrial cancer, especially in high‐risk populations, though the mechanism behind the association remains unknown.